Phar phyin ʼgrel mchan gźan phan snaṅ ba : a commentary expanding the text of the Abhisamayālaṅkāra - Gźan-phan-chos-kyi-snaṅ-ba, Gźan-dgaʼ, 1871-1927 (Lopon Gyatsho, 1978)
Buddhist Prajñāpāramitā philosophy.